Assembly processes of abundant and rare microbial communities in orchard soil under a cover crop at different periods - Zhao, Zhiyuan; Ma, Yanting; Feng, Tianyu; Kong, Xu; Wang, Zhaohui; Zheng, Wei; Zhai, Bingnian (Geoderma, 2022)
•Diversities of abundant and rare taxa exhibited a similar response to cover crop.•Only the fungal subcommunities structures were affected by cover crop.•Assembly of abundant bacteria was affected by cover crop rather than growth period.•Assembly of abundant and rare fungi were not affected by growth period and cover crop.•The assembly processes of each subcommunity were driven by distinct soil factors. Soil microorganisms play key roles in agricultural ecosystems. However, little is known about their dynamic diversity patterns and community assembly processes, especially in the rare microbial biosphere in agriculture systems. In this study, we determined the responses of diversities and assembly processes of abundant and rare bacterial and fungal subcommunities to agricultural practice (i.e. cover crop) in a semiarid orchard soil by using 16S and ITS rRNA gene sequencing. We found that the community structures of abundant and rare taxa exhibited a similar response to cover crop or growth periods. Growth periods significantly changed the bacterial and fungal subcommunities structure. Only the fungal subcommunities structure was affected by cover crop. The community assembly of abundant and rare fungi was respectively dominated by stochastic process and deterministic process and less affected by cover crop and growth period. For abundant bacteria, the assembly process was dominated by heterogeneous and undominated processes, and the importance of heterogeneous selection process was increased by cover crop at setting and maturing period. The assembly process of rare bacterial community was dominated by a homogeneous selection and the relative importance of dispersal limitation was increased at maturing period. We also found that the assembly processes of abundant taxa were significantly related to the soil DON, NH4+-N, NO3–-N and pH, while the assembly processes of rare taxa were significantly related to the soil DOC, AP and SOC. Our results provide new insights into the formation of the microbial community in orchard soil under a cover crop, especially the seasonal succession of abundant and rare bacterial and fungal subcommunities.